Creating Knowledge in and About Conflicted Contexts: How Peacekeepers Know What Works - Furnari, Ellen (Thammasat Review, 2022)
This paper discusses the knowledge creation processes of peacekeepers, based on research with former peacekeepers who served as military, police, civilians or unarmed civilian peacekeepers, as well as my own process as a peace researcher. Peacekeepers report knowing what is effective through their embodied and performed experiences which occur in relationship. Their ways of knowing are relational and impacted by the organisations and contexts in which they work and their own beliefs and orientations. This has implications for the processes of creating knowledge and the practice of interventions intended to prevent violence and protect people in conflict affected communities. Keywords: Peacekeeping, Knowledge creation, Violence prevention, Peace and conflict studies.